Polymyxin Resistance in Clinical Isolates of K. pneumoniae in Brazil: Update on Molecular Mechanisms, Clonal Dissemination and Relationship With KPC-Producing Strains - Conceição-Neto, Orlando C.; da Costa, Bianca Santos; Pontes, Leilane da Silva; Silveira, Melise Chaves; Justo-da-Silva, Lívia Helena; de Oliveira Santos, Ivson Cassiano; Teixeira, Camila Bastos Tavares; Tavares e Oliveira, Thamirys Rachel; Hermes, Fernanda Stephens; Galvão, Teca Calcagno; Antunes, L. Caetano M.; Rocha-de-Souza, Cláudio Marcos; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
In Brazil, the production of KPC-type carbapenemases in Enterobacteriales is endemic, leading to widespread use of polymyxins. In the present study, 502 Klebsiella pneumoniae isolates were evaluated for resistance to polymyxins, their genetic determinants and clonality, in addition to the presence of carbapenem resistance genes and evaluation of antimicrobial resistance. Resistance to colistin (polymyxin E) was evaluated through initial selection on EMB agar containing 4% colistin sulfate, followed by Minimal Inhibitory Concentration (MIC) determination by broth microdilution. The susceptibility to 17 antimicrobials was assessed by disk diffusion. The presence of blaKPC, blaNDM and blaOXA-48-like carbapenemases was investigated by phenotypic methods and conventional PCR. Molecular typing was performed by PFGE and MLST. Allelic variants of the mcr gene were screened by PCR and chromosomal mutations in the pmrA, pmrB, phoP, phoQ and mgrB genes were investigated by sequencing. Our work showed a colistin resistance frequency of 29.5% (n = 148/502) in K. pneumoniae isolates. Colistin MICs from 4 to >128 µg/mL were identified (MIC50 = 64 µg/mL; MIC90 >128 µg/mL). All isolates were considered MDR, with the lowest resistance rates observed for amikacin (34.4%), and 19.6% of the isolates were resistant to all tested antimicrobials. The blaKPC gene was identified in 77% of the isolates, in consonance with the high rate of resistance to polymyxins related to its use as a therapeutic alternative. Through XbaI-PFGE, 51 pulsotypes were identified. MLST showed 21 STs, with ST437, ST258 and ST11 (CC11) being the most prevalent, and two new STs were determined: ST4868 and ST4869. The mcr-1 gene was identified in 3 K. pneumoniae isolates. Missense mutations in chromosomal genes were identified, as well as insertion sequences in mgrB. Furthermore, the identification of chromosomal mutations in K. pneumoniae isolates belonging from CC11 ensures its success as a high-risk epidemic clone in Brazil and worldwide.